Analytical Study of Trends in Measuring Sustainability Performance and Indexes - Harpito Jasri; Insannul Kamil; Dicky Fatrias; Feri Afrinaldi; Alexie Herryandie B.A (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
Sustainability was a crucial underpinning for addressing and mitigating the impacts of climate change. It was not only considered a moral responsibility but also a key element in building a sustainable future. The measurement of sustainability index and performance played a very important role in various sectors because it provided an objective basis for evaluating the economic, social, and environmental impacts of a company or organization's activities. Various sectors needed to play a key role through the implementation of integrated sustainability activities, including efforts to reduce pollution, utilize resources efficiently, increase engagement with communities as stakeholders, and ensure sustainable economic progress. This study aimed to explore and analyze the trend of measuring sustainability index and performance that were developing from various relevant literature through a systematic literature review. The method used in this study was a systematic literature review by adopting the PRISMA-P stages. The PICOS Framework was used in compiling inclusion and exclusion criteria. The PRISMA-P 2020 protocol was employed in the screening process, and VOSviewer was used in the bibliometric analysis. Based on the analysis, it was concluded that research related to sustainability in the higher education and construction project sectors was important to explore further. The most popular method used was the mixed method, while observation and questionnaires were the most widely used data collection methods.Keywords: sustainability, index measurement, performance measurement, systematic literature review.